Supramolecular Hemicage Cobalt Mediators for Dye‐Sensitized Solar Cells. Issue 23 (11th October 2016) - Freitag, Marina; Yang, Wenxing; Fredin, Lisa A.; D'Amario, Luca; Karlsson, K. Martin; Hagfeldt, Anders; Boschloo, Gerrit
Abstract: A new class of dye‐sensitized solar cells (DSSCs) using the hemicage cobalt‐based mediator [Co(ttb)] 2+/3+ with the highly preorganized hexadentate ligand 5, 5′′, 5′′′′‐((2, 4, 6‐triethyl benzene‐1, 3, 5‐triyl)tris(ethane‐2, 1‐diyl))tri‐2, 2′‐bipyridine (ttb) has been fully investigated. The performances of DSSCs sensitized with organicD –π–A dyes utilizing either [Co(ttb)] 2+/3+ or the conventional [Co(bpy)3 ] 2+/3+ (bpy=2, 2′‐bipyridine) redox mediator are comparable under 1000 W m −2 AM 1.5 G illumination. However, the hemicage complexes exhibit exceptional stability under thermal and light stress. In particular, a 120‐hour continuous light illumination stability test for DSSCs using [Co(ttb)] 2+/3+ resulted in a 10 % increase in the performance, whereas a 40 % decrease in performance was found for [Co(bpy)3 ] 2+/3+ electrolyte‐based DSSCs under the same conditions. These results demonstrate the great promise of [Co(ttb)] 2+/3+ complexes as redox mediators for efficient, cost‐effective, large‐scale DSSC devices. Abstract : A stable redox mediator : The use of a highly pre‐organized hemicage hexadentate ligand for cobalt‐based redox mediators in mesoscopic dye‐sensitized solar cells (DSSCs) considerably improves the thermal and light stability of the new [Co(ttb)] 2+/3+ over the commonly used [Co(bpy)3 ] 2+/3+ redox couple. The performances of DSSCs sensitized with organic D–π–A dyes utilizing either [Co(ttb)] 2+/3+ or [Co(bpy)3 ] 2+/3+ are comparable under 1000 W m −2 AM 1.5 G illumination.